Hubungan Antara Kepuasan Kerja Dengan Organizational Citizenship Behavior ( OCB ) Pada Karyawan RS PKU Muhammadiyah Surakarta - Urbach, Arwin Analla; , Achmad Dwityanto, S.Psi, M.Si (2017)
The aim of this research is to know is there a relationship between work satisfaction and organizational citizenship behavior on RS PKU Muhammadiyah Surakarta employees. The hypothesis proposed that there are positive relathionship between work satisfication and organizational citizenship behavior on RS PKU Muhammadiyah Surakarta employees. Researcher used proportional random sampling to determine the subjects of research, there are 100 respondents. This research used quantitative methods with work satisfication scale and organizational citizenship behavior scale as a measurement. Data analysis on this research using SPSS 19.0 with product-moment correlation method, obtained 0,769 of coreelation coeffisien and 0,000 (p≤0,01) of significant (p) which showed that there is a positive relationship between work satisfaction and organizational citizenship behavior. Effective donation from two variable showed by R2 = 0,591 it means work satisfaction affects by 59,1 % to organizational citizenship behavior and there is 40,9% affected by other. Work Satisfaction on RS PKU Muhammadiyah Surakarta employees relatively high with empirical average (EA) = 141,71 and hipotetical average (HA) = 115. Organizational Citizenship Behavior on RS PKU Muhammadiyah Surakarta employees relatively high with empirical average (EA)= 141,57 and hipotetical average (HA) = 115.